Development of an Online Exhibition using Inquiry-Based Learning Management - Noiumkar, Siriporn (Journal of Applied Informatics and Technology, 2024)
The research aimed at 1) developing an online exhibition through inquiry-based learning management for Book Fair at Academic Resource Centre, Mahasarakham University case study, 2) evaluating the quality of the online exhibition, and 3) studying the visitors’ perception towards the online exhibition through inquiry-based learning management. By using Krejcie and Morgan table to determine the sample size, there were 132 Mahasarakham University students participating in the study. The research tools included 1) the online exhibition through inquiry-based learning, 2) the questionnaire for experts regarding the quality of the online exhibition, and 3) the questionnaire for visitors' perception towards the online exhibition based on the principles of inquiry-based learning. The research findings indicated that the online exhibition using inquiry-based learning management consists of 1) the aspect of engagement, 2) the aspect of exploration, 3) the aspect of explanation, 4) the aspect of elaboration, and 5) the aspect of evaluation. The exhibition was presented in a three-dimensional virtual reality format where visitors could experience the content of the online exhibition by navigating through the virtual world as if they were walking through an actual exhibition. The evaluation results of the online exhibition’s quality was at excellent level with the mean value of 4.61. The students’ perceptions when visiting the online exhibition was at high level with the mean value of 4.35. It indicated that the online exhibition could convey its content and story very well. It also allowed visitors to have interactions through chats, conversations, virtual walking in a 3D virtual reality, and freely explore the desired content that were presented in the forms of videos, images, texts, and live broadcasting. This could greatly enhance visitor’s perception and create new experience for them.